PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN-PERUSAHAAN PADA SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - B51108103, Sufhia Leka (Jurnal KIAFE, 2013)
The results are (1) The first hypothesis is rejected because the activity of board commissioners has a negative and not significant impact on financial performance (2) The second hypothesis is rejected because the size of the board of directors has a negative and not significant impact on financial performance (3) The third hypothesis is rejected because the size of the independent commissioners has a positive and not significant impact on financial performance, and (4) The fourth hypothesis is accepted because the audit committee has a positive and significant impact on financial performance. Keywords: The size of Board Commissioners, The Size of The Board of Directors, The Size of The Independent Commissioners, Audit Committee and Financial Performance (CFROA).